Remedial urban planning: an amplifying factor of natural risks in urban environments. The case of the Grand Nador Agglomeration, Morocco - El-Amrani, Hassan; Abdellatif, Tribak (Revista de Estudios Andaluces, 2023)
Grand Nador is characterised by a deep spatial and territorial dynamic linked to the economic, social and environmental changes of this territory. In proportion to this size dynamic, urbanization experiences enormous difficulties. Without worrying about the presence of natural risks, often concealed in a punctual and curative territorial management of a remedial urbanism, this territory has seen its vulnerability increased. The more there is the urbanization crisis, the more there is recourse to the catch-up mechanism, so the catch-up provisions only make urban management more complex, these operations do not yet reflect the integration of these districts into the overall plan. To grasp the relationship between this remedial urban planning and the acceleration of natural risks. A holistic approach was deployed, several approaches were adopted: So, if the historical approach was useful to know the birth of this derailed urbanization, the work sessions and the questionnaire were very beneficial to measure territorial parameters. While the excursions were an opportunity to compare the results obtained with reality.